Sociology in a crisis: Covid-19 and the colonial politics of knowledge production in Aotearoa New Zealand. (December 2020) - Barber, Simon; Naepi, Sereana
Rather than being exceptional for Māori and Pacific Peoples, Covid-19 is the latest iteration of virulent disease that arrived with European colonisation. The various pandemics are connected; they exacerbate and intensify existing conditions of colonial inequality and injustice. The political and economic marginalisation of Māori and Pasifika within Aotearoa New Zealand ensures that Covid-19 will have disproportionate impacts upon them. Covid-19's impacts will be felt in the academy as everywhere else. The immediate issue will be the culling of less popular 'uneconomic' courses, and of precarious instructors (where Māori and Pacific teachers are over-represented). Colonisation never ended. Ongoing domination is secured through the reproduction of social life, including via social institutions like the university. While sociology likes to think of itself as the critical edge, it often fails to be so in relation to its own assumptions. In order for sociology to be part of the solution, instead of simply perpetuating the problem of racism as it is wont to do, its practitioners must recognise our place in the world, must speak to our ways of knowing and being, and must validate the aspirations of Māori and Pacific communities, Māori and Pacific students and Māori and Pacific staff.